Antara Teori dan Realitas: Refleksi Filosofis dan Interpretasi Kosmologi Kuantum - M. Abu Kamal; Fitriya S (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Einstein's General Theory of Relativity has revolutionized our understanding of gravity by replacing Newtonian gravitational law, which regarded gravity as an attractive force between two masses. In GR, gravity is seen as a manifestation of the geometry of spacetime, influenced by the distribution of mass and energy. This theory successfully explains phenomena such as the bending of light by massive objects and the prediction of the existence of black holes. Meanwhile, Quantum Mechanics, rooted in the works of Max Planck, Albert Einstein, Niels Bohr, and Werner Heisenberg, reveals a microscopic world filled with probabilities and uncertainties, as well as phenomena such as wave-particle duality and Heisenberg’s uncertainty principle. While both theories have successfully explained phenomena at macroscopic and microscopic scales, the inability to unify General Relativity and Quantum Mechanics remains a major issue in theoretical physics. The fundamental differences between them, particularly regarding the nature of spacetime and determinism, create challenges in formulating a theory of quantum gravity. Various approaches, such as Loop Quantum Gravity (LQG) and string theory, aim to unify these two theories, although they still face limitations in experimental verification. Quantum cosmology also opens up space for deeper philosophical reflections on the nature of reality, spacetime, determinism, and the role of the observer in determining physical existence, leading to questions regarding the meaning and purpose of the universe itself within its underlying probabilistic and uncertain framework.